Scaling Properties of a Hybrid Fermi-Ulam-Bouncer Model - Oliveira, Diego F. M. [UNESP]; Bizao, Rafael A. [UNESP]; Leonel, Edson Denis [UNESP] (Hindawi Publishing Corporation, 2009)
Some dynamical properties for a one-dimensional hybrid Fermi-Ulam-bouncer model are studied under the framework of scaling description. The model is described by using a two-dimensional nonlinear area preserving mapping. Our results show that the chaotic regime below the lowest energy invariant spanning curve is scaling invariant and the obtained critical exponents are used to find a universal plot for the second momenta of the average velocity. Copyright (C) 2009 Diego F. M. Oliveira et al.